Targeting PRSS23 with tipranavir induces gastric cancer stem cell apoptosis and inhibits growth of gastric cancer via the MKK3/p38 MAPK-IL24 pathway - Xiong Ji-xian; Li Yu-ting; Tan Xiang-yu; Chen Tie; Liu Bao-hua; Fu Li (Acta Pharmacologica Sinica; Vol 45, No 2 (February 2024): Acta Pharmacologica Sinica, 2024)
Gastric cancer stem cells (GCSCs) contribute to the refractory features of gastric cancer (GC) and are responsible for metastasis, relapse, and drug resistance. The key factors drive GCSC function and affect the clinical outcome of GC patients remain poorly understood. PRSS23 is a novel serine protease that is significantly up-regulated in several types of cancers and cancer stem cells, and related to tumor progression and drug resistance. In this study, we investigated the role of PRSS23 in GCSCs as well as the mechanism by which PRSS23 regulated the GCSC functions. We demonstrated that PRSS23 was critical for sustaining GCSC survival. By screening a collection of human immunodeficiency virus (HIV) protease inhibitors (PIs), we identified tipranavir as a PRSS23-targeting drug, which effectively killed both GCSC and GC cell lines (its IC50 values were 4.7 and 6.4 μM in GCSC1 cells and GCSC2 cells, respectively). Administration of tipranavir (25 mg·kg−1·d−1, i.p., for 8 days) in GCSC-derived xenograft mice markedly inhibited the growth of subcutaneous GCSC tumors without apparent toxicity. In contrast, combined treatment with 5-FU plus cisplatin did not affect the tumor growth but causing significant weight loss. Furthermore, we revealed that tipranavir induced GCSC cell apoptosis by suppressing PRSS23 expression, releasing MKK3 from the PRSS23/MKK3 complex to activate p38 MAPK, and thereby activating the IL24-mediated Bax/Bak mitochondrial apoptotic pathway. In addition, tipranavir was found to kill other types of cancer cell lines and drug-resistant cell lines. Collectively, this study demonstrates that by targeting both GCSCs and GC cells, tipranavir is a promising anti-cancer drug, and the clinical development of tipranavir or other drugs specifically targeting the PRSS23/MKK3/p38MAPK-IL24 mitochondrial apoptotic pathway may offer an effective approach to combat gastric and other cancers.